(untitled) (International Journal of Food and Nutritional Sciences, 2019)
This study provides a critical analysis of Kiran Desai’s writings, focusing on her stylistic choices and thematic explorations. The author’s unique narrative approach and her exploration of themes such as globalization and identity are examined. The study finds that Desai’s works offer a nuanced perspective on the human condition, blending the personal with the political. The discussion underscores the significance of her storytelling in portraying the complexities of contemporary society. In conclusion, Desai’s writings emerge as a compelling exploration of the intersection between individual lives and broader societal narratives.